2017
DOI: 10.4103/0253-7176.198945
|View full text |Cite
|
Sign up to set email alerts
|

Adult Attention Deficit Hyperactivity Disorder in Patients with Substance Use Disorders: A Study from Southern India

Abstract: Context:Externalizing disorders of childhood characterized by attention deficit hyperactivity disorder (ADHD), conduct disorder and oppositional defiant disorder are well known to predispose an individual to experiment with substances at an early age and the later lead to the development of substance use disorders (SUD). ADHD, a developmental disorder, persists into adulthood in about two-thirds of the cases.Aims:In the present study, we aimed to explore the prevalence of ADHD and its subtypes in treatment-see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The findings from the current study are similar to earlier studies in India and from other countries. [1,2,4] Subjects with ADHD had a relatively faster progression of the disease process. This is reflected in the significantly earlier age of onset of craving, higher amount of alcohol use, tolerance, withdrawal symptoms, salience, and early morning use among these patients in the current sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings from the current study are similar to earlier studies in India and from other countries. [1,2,4] Subjects with ADHD had a relatively faster progression of the disease process. This is reflected in the significantly earlier age of onset of craving, higher amount of alcohol use, tolerance, withdrawal symptoms, salience, and early morning use among these patients in the current sample.…”
Section: Discussionmentioning
confidence: 99%
“…ADHD persists into adulthood among the majority of the affected children. [12] However, with the increasing age, the symptom manifestation changes considerably: the hyperactivity decreases, while the inattention and impulsivity persist. [3] Studies around the world have shown that the prevalence of childhood ADHD in the general population ranges 5%-12% while the prevalence of adult ADHD ranges 2%-6%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This replicates similar findings from our previous studies on ADHD and SUD. [ 2 3 ] The MR for ADHD and other externalizing spectrum disorders in children of all alcohol dependents was high, especially with the patients of EO of dependence. Furthermore, the probability of developing alcohol dependence in children of EO patients was much more.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Our previous study in a treatment cohort from India suggested that the rates of comorbidity of ADHD and SUD are around 21.7%. [ 2 ] Another study from our center found that there were higher odds of ADHD in individuals with early onset (EO) of alcohol-dependence syndrome (ADS) defined as ADS established by the age of 25 years or earlier. [ 3 ] Furthermore, the SUD and related problems are severe, and outcomes are poorer in individuals with ADHD than those without ADHD.…”
Section: Introductionmentioning
confidence: 99%